Pendidikan Islam dan Perannya dalam Membentuk Karakter Mahasiswa - Astuti, Mardiah; Herlina, Herlina; Ibrahim, Ibrahim (Universitas Pendidikan Mandalika, 2024)
Abstract: This research discusses Islamic education and its role in shaping the character of students. The focus of this study is the students of the Islamic Education Study Program (MPI C) of the 2022 cohort at UIN Raden Fatah Palembang. The research is qualitative with a descriptive approach. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve the stages of data collection, data presentation, verification, and drawing conclusions. To ensure the validity of the data, the researcher uses data triangulation, consisting of triangulation of time, methods, and sources. The results obtained indicate that the implementation of Islamic education and its role in shaping the character of students has been carried out effectively through various programs, including activities for the development of morals and personality, instilling Islamic values through learning, and character education activities for students. All these activities have a positive impact on developing the moral principles and ethics of students, as well as their ability to empathize, show compassion, and take social responsibility. They also contribute to helping students develop good personalities, grow, and prepare them to become morally upright individuals.Keywords: Islamic Education, Character FormationAbstrak: Penelitian ini membahas tentang pendidikan Islam dan perannya dalam membentuk karakter mahasiswa. Fokus penelitian ini yakni mahasiswa MPI C Angkatan 2022 UIN Raden Fatah Palembang. Jenis penelitian adalah kualitatif dengan pendekatan deskriptif. Metode pengumpulan data melalui wawancara, observasi dan dokumentasi. Teknik analisis data melalui tahapan pengumpulan data, penyajian data dan verifikasi serta penarikan kesimpulan. Untuk memeriksa keabsahan data, maka peneliti menggunakan triangulasi data, yang terdiri dari triangulasi waktu, metode dan sumber. Hasil yang diperoleh bahwa pelaksanakan pendidikan Islam dan perannya dalam membentuk karakter mahasiswa sudah dilaksanakan dengan baik melalui beberapa program, diantaranya kegiatan pembentukan akhlak dan kepribadian, penanaman nilai-nilai keislaman melalui pembelajaran dan kegiatan pendidikan karakter bagi mahasiswa. Semua kegiatan itu memiliki dampak yang baik dalam mengembangkan prinsip-prinsip moral dan etika mahasiswa serta kemampuan mereka untuk berempati, berbelas kasih, dan tanggung jawab sosial, juga untuk membantu mahasiswa memiliki kepribadian yang baik, tumbuh dan mempersiapkan mereka menjadi mahasiswa yang bermoral.Kata Kunci: Pendidikan Islam, Pembentukan Karakter